Evaluation of inner segment/outer segment junctions in different types of epiretinal membranes - Aydın,Rukiye (2016)
ABSTRACT Purpose: This study was conducted to evaluate the relationships of inner/outer segment (IS/OS) junction disruption, macular thickness, and epiretinal membrane (ERM) grade with best-corrected visual acuity (BCVA), as well as the relationship between IS/OS junction disruption and ERM grade. Methods: Fifty-four eyes of 54 patients with different grades of ERM were retrospectively reviewed. Patients were classified into three groups by ERM grade according to retinal striae and vessel distortion: grade/group 1, visible membranes without retinal striae or vessel distortion; grade/group 2, mild to moderate macular striae or vessel straightening; and grade/group 3, moderate to severe striae and vascular straightening. Correlations of BCVA with age, central retinal thickness, ERM grade, and IS/OS disruption as well as of IS/OS disruption, central macular thickness, and BCVA with ERM grade were evaluated. Results: Twenty-nine (53.7%) eyes exhibited IS/OS junction disruption. Groups 1 and 2 differed significantly with respect to BCVA (p=0.038), but groups 2 and 3 did not (p=0.070). Central macular thickness was significantly greater in group 2 than in group 1 (p=0.031) and in group 3 than in group 2 (p=0.033). Groups 1 and 2 differed significantly in terms of IS/OS disruption (p=0.000), but groups 2 and 3 did not (p=0.310). Conclusions: The IS/OS junction appears to be disrupted during the early stages of ERM. Grade 3 ERM is associated with a significantly higher incidence of IS/OS disruption.